The Implementation of Project Based Learning Model in Improving Islamic Religious Education Learning Outcomes at SMK Yaspi Labuhan Deli - Rabilla, Kaisyah (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to examine the implementation of the Project Based Learning (PjBL) model in improving students’ learning outcomes in Islamic Religious Education (PAI) at SMK Yaspi Labuhan Deli. The research method applied was classroom action research conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 30 eleventh-grade students. The instruments used included observation sheets, learning outcome tests, and documentation. The findings revealed that the application of PjBL improved students’ engagement during the learning process as well as their learning outcomes in Islamic Religious Education. In the first cycle, the students’ average achievement was categorized as fair, while in the second cycle, it improved to the good category. Therefore, it can be concluded that the implementation of Project Based Learning is effective in optimizing Islamic Religious Education learning outcomes at SMK Yaspi Labuhan Deli.